(untitled) (CIPEEX, 2025)
This study will highlight the importance of Brazilian agribusiness; the main implications of the misuse of agricultural pesticides for the health of rural workers; the laws that govern and regulate the use of pesticides in Brazil; the civil and labor liability of employers; and the difficulties in proving the causal link between harm to workers and contact with pesticides. The methodology used will be qualitative, based on studies of articles, the Federal Constitution, and the Civil Code. With regard to the results, it will be possible to observe that several authors have already proven the relationship between contact with pesticides and various diseases, which can even occur in the long term, and because of this, there is difficulty in proving the causal link in this situation.